Glycemic control among individuals with self-reported diabetes in India--the ICMR-INDIAB Study - Unnikrishnan, Ranjit; Anjana, Ranjit Mohan; Deepa, Mohan; Pradeepa, Rajendra; Joshi, Shashank R; Bhansali, Anil; Dhandania, Vinay K; Joshi, Prashant P; Madhu, Sri Venkata; Rao, Paturi Vishnupriya; Lakshmy, Ramakrishnan; Jayashri, Ramamurthy; et al. (Diabetes technology & therapeutics, 2014)
This study estimated the levels of glycemic control among subjects with self-reported diabetes in urban and rural areas of four regions in India. Phase I of the Indian Council of Medical Research-India Diabetes (ICMR-INDIAB) Study was conducted in a representative population of three states of India (Tamil Nadu, Maharashtra, and Jharkhand) and one Union Territory (Chandigarh) and covering a population of 213 million people. Using a stratified multistage sampling design, individuals ≥20 years of age were recruited. Glycemic control among subjects with self-reported diabetes was assessed by measurement of glycated hemoglobin (HbA1c), estimated by the Variant™ II Turbo method (Bio-Rad, Hercules, CA). Among the 14,277 participants in Phase I of INDIAB, there were 480 subjects with self-reported diabetes (254 urban and 226 rural). The mean HbA1c levels were highest in Chandigarh (9.1±2.3%), followed by Tamil Nadu (8.2±2.0%), Jharkhand (8.2±2.4%), and Maharashtra (8.0±2.1%). Good glycemic control (HbA1c <7%) was observed only in 31.1% of urban and 30.8% of rural subjects. Only 22.4% of urban and 15.4% of rural subjects had reported having checked their HbA1c in the past year. Multiple logistic regression analysis revealed younger age, duration of diabetes, insulin use, and high triglyceride levels to be significantly associated with poor glycemic control. The level of glycemic control among subjects with self-reported diabetes in India is poor. Urgent action is needed to remedy the situation.